2007
DOI: 10.1152/ajprenal.00162.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of pelvic nerve afferents and mast cell infiltration in the urinary bladder following chronic colonic irritation is mediated by neuropeptides

Abstract: Irritable bowel syndrome and interstitial cystitis frequently overlap. We have shown that acute colitis sensitizes urinary bladder afferents to both mechanical and chemical stimuli and that chronic colitis similarly produces neurogenic cystitis. We hypothesize that chronic irritation of the colon releases neuropeptides from bladder afferents, leading to receptor sensitization and neurogenic inflammation. Female Sprague-Dawley rats received intrarectal trinitrobenzenesulfonic acid (TNBS) or vehicle 3 days follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 47 publications
8
80
1
2
Order By: Relevance
“…There is a growing literature demonstrating "cross talk" between the bladder and the colon at the level of neural signaling (34,35), and this neuronal cross talk likely also involves the uterus (41). To test the possible role of such cross talk in the development of pelvic pain behavior, we also assessed pelvic sensitivity to mechanical stimuli following instillation of 2% lidocaine into the colon or uterus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing literature demonstrating "cross talk" between the bladder and the colon at the level of neural signaling (34,35), and this neuronal cross talk likely also involves the uterus (41). To test the possible role of such cross talk in the development of pelvic pain behavior, we also assessed pelvic sensitivity to mechanical stimuli following instillation of 2% lidocaine into the colon or uterus.…”
Section: Resultsmentioning
confidence: 99%
“…For example, mustard oil administered to the uterine horn or colon in female rats induced vascular permeability in the bladder consistent with inflammation at a site distinct from the inflammatory stimulus (41). This cross talk is at least partially bidirectional, because bladder irritation also sensitized the colon to distension stimuli (28), and this noxious effect can be mediated by either chemical or mechanical stimuli (11,34,35). It is not known whether neurogenic cystitis also involves cross talk, but these previous findings suggest that organ cross talk may be exploited for therapeutic approaches to pelvic pain.…”
mentioning
confidence: 99%
“…Our previous findings showed that intracolonic application of RTX can cause massive release of substance P and calcitonin gene-related peptide from the bladder afferent terminals leading to the development of a neurogenic bladder over a period of time (34). Ustinova and colleagues (45) determined that chronic colonic irritation sensitized urinary bladder afferents to noxious stimuli and caused mast cell infiltration in the bladder. The latter effects were reversed by systemic administration of the TRPV1 agonist capsaicin, suggesting the involvement of TRPV1 receptors in colon-bladder cross talk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies have established a correlation between structural pathophysiological changes in the directly affected pelvic organs and secondary dysfunctions developed in adjacent pelvic structures (9,27,28,36). It has been determined that colonic inflammation causes hyperactivity of bladder afferent fibers (44), hyperexcitability of bladder projecting sensory (27, 28) and spinal (38) neurons, increased release of proinflammatory neuropeptides in the urinary bladder (34,45), and changes in the detrusor contractility (32). However, the exact pathways of transmission of nociceptive information from the inflamed colon to the urinary bladder as well as receptors and molecules activated during this transmission remain elusive.…”
mentioning
confidence: 99%
“…Of note, women experiencing CPP often exhibit overlapping symptoms of BPS/IC and IBS [76]. Much of this overlap can be attributed to central and peripheral neural mechanisms of pelvic organ cross-sensitization [77][78][79]. However, the juxtaposition of SP-positive nerve fibers and MCs [80] may play an important role in pelvic organ cross-sensitization by amplifying afferent signaling.…”
Section: Role Of Mcs In Pain Processesmentioning
confidence: 99%